Kepemimpinan Kepala Sekolah dalam Mewujudkan Merdeka Belajar pada Sekolah Menengah Kejuruan (SMK) - Kholifatul Husna Asri (Jurnal Administrasi Pendidikan, 2023)
This research was conducted to examine how the role of school principal leadership in realizing independent learning that can produce graduates according to the needs and demands of IDUKA. The method used in this research is a qualitative approach. This research was conducted at SMK Negeri Kota Bogor. The results of this study indicate that in realizing independent learning at school, the role of the principal as 1) leader is needed, the principal is sufficiently understanding about the important points of independent learning, this is shown through the principal's response which is realized in activity programs in schools that are oriented towards competence of teacher expertise. And supported by efforts to build communication and openness between school principals and teachers so that trust is created in each other, and 2) managers, principals utilize and develop resources in schools including coaching teachers, as an important element in carrying out a learning process that can produce qualified graduates. This effort is made through a teacher apprenticeship program. In addition, the principal encourages teachers to be creative and innovative so that they can create an achievement through the work they produce.